Prototype System Water Level Reservoir untuk Pengendalian Kelebihan Air Dengan Mikrokontroller Arduino Uno R3 - Budi Yannur; Didit Suprihanto; Happy Nugroho; Aji Ery Burhandenny; Restu Mukti Utomo (Jurnal Pendidikan Informatika (EDUMATIC), 2021)
PDAM Loa Kulu Branch still uses sticks or poles as an indicator of the water level in the reservoir. Reservoir is a place to store clean water production from PDAM, the weakness of using sticks or poles is when the operator does not monitor continuously causing air loss when production becomes large. The goal of the study was to design a water-level prototype to control excess water in the reservoir. The method used is a prototype with the stage of gathering information through interviewing PDAM staff, creating and repairing prototypes and testing prototypes. The test used hardware consisting of arduino uno r3, ultrasonic sensor hc-sr04, flowmeter sensor yf-s201, 16 x 2 lcd, relay module, buzzer, solenoid valve 12 V_dc, pump 12 V_dc and display measurement results in the visual studio application 2019. Our findings are that the length of reservoir charging with an average input discharge of 3.6 liters / minute is 2.93 minutes. As for the length of emptying the reservoir with an average output discharge of 1.06 liters / minute is 12.10 minutes. The conclusion of this study is that the system can monitor the water level inside the reservoir automatically and know the time needed for the feeling and emptying process of the reservoir.